A Modified Pre-Auricular Approach in the Treatment of Orbital Zygomatic Maxillary Complex Fractures. Issue 7 (October 2018) - Tang, Weiwei; Zhu, Huimin; Li, Zhengkang; Deng, Yuan
Abstract : Objective: This study aimed to evaluate the safety of a modified pre-aricular approach in the treatment of orbital zygomatic maxillary complex fractures. Methods: This was a retrospective study of clinical data from 108 adults who were diagnosed with orbital zygomatic maxillary complex fractures and undergo open reduction and internal fixation through a modified pre-auricular approach. Exophthalmometry and limitation of extraocular muscle movement were determined using a Hertel exophthalmometer or synoptophore examination respectively. Primary complications were recorded, and postoperative facial nerve injury was tested by electrophysiologic analysis. Results: All patients received satisfied functional and cosmetic results at least 6 moths postoperatively. There were 2 cases (1.85%) involving complete or incomplete facial nerve injury confirmed by electrophysiologic analysis. The incidence of other postoperative complications including a hematoma rate of 1.85% patients and permanent hypesthesia or paresthesia in 2.78% of patients, and no cases of clinically significant temporal hollowing, alopecia, infection, or unacceptable scars encountered during a mean follow-up period of 2 years. Conclusion: A modified pre-auricular approach with dissection deep to the temporalis fascia offers a safe and reliable surgical technique for accessing the malar arch in orbital zygomatic maxillary complex fractures.